A visita de irmãos na unidade de terapia intensiva: implicações na saúde do bebê e nas relações familiares. - Fernandes, Priscila Brennand de Carvalho (2020)
This paper aims to reflect on the visit of siblings to the newborn at risk, more specifically on the way in which the child's entry into the neonatal intensive care unit contributes to the construction of a more significant parental bond with the baby within this hospital context. For this, an analysis was made from the perspective of Winnicott as to the relevance of this bond for the baby and as to the aspects that may affect this bond from the moment the newborn is hospitalized right after birth in an incubator. It was found that the newborn's brother's entry into this space calls on parents and staff to look at the newborn as a subject beyond his clinical condition. In this scene, what stands out is the neonate's meaning for the family, as it is part of their stories. This recognition favors the identification of caregivers with the newborn.